Localized Transient Stability (LTS) Method for Real-time Localized Control - Abdul Malek Miah (International Journal of Applied Power Engineering (IJAPE), 2018)
Very recently, a new methodology was introduced solely for the purpose of real-time localized control of transient stability. The proposed new method is based on the localized transient stability of a power system. This is completely a new idea in transient stability. In this method, the post-fault power system is represented by a two-generator localized power system at the site of each individual generator. If each of these localized power systems reaches its respective stable equilibrium, then the full power system also reaches its stable equilibrium. Therefore, in terms of real-time localized control of transient stability, if each of the localized power systems is driven to its respective stable equilibrium by local control actions with local computations using the locally measured data, then the full power system is driven to its stable equilibrium. Thus the method can be easily implemented for real-time localized control of transient stability. In this paper, the details of the mathematical formulations are presented. Some interesting test results on the well-known New England 39-bus 10-generator system are also presented in this paper to demonstrate the potential of the proposed method for use in real-time localized control of transient stability.